2003
DOI: 10.1515/tjj.2003.20.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Control of Suddenly Expanded Flows with Micro-Jets

Abstract: The results of an experimental investigation carried out to control the base pressure in a suddenly expanded axisymmetric passage are presented in this paper. Active control in the form of micro-jets was employed to control the base pressure. Air injection at four locations at the base, symmetric to the nozzle axis, was used as the active control. The jet Mach numbers at the entry to the suddenly expanded duct studied were 1.87, 2.2 and 2.58. The length-to-diameter ratio of the suddenly expanded duct was varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 14 publications
2
45
0
Order By: Relevance
“…Rathakrishnan and Sreekanth [6]conducted experiments through circular pipes and from their tests they found that the pressure in the base area is a function of area of enlargement of the duct, the level of expansion and the inertia level. [7][8][9][10][11][12][13][14] investigated the efficacy of the tinyjets as the flow regulator in the base corner for flows from C-D nozzles under the circumstances that at the exit of the nozzle adverse pressure gradientpersists for Mach numbers 2.0, 2.5, and 3.0. A maximum gain of 80 % in the base pressure was accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Rathakrishnan and Sreekanth [6]conducted experiments through circular pipes and from their tests they found that the pressure in the base area is a function of area of enlargement of the duct, the level of expansion and the inertia level. [7][8][9][10][11][12][13][14] investigated the efficacy of the tinyjets as the flow regulator in the base corner for flows from C-D nozzles under the circumstances that at the exit of the nozzle adverse pressure gradientpersists for Mach numbers 2.0, 2.5, and 3.0. A maximum gain of 80 % in the base pressure was accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Pe/Pa = <> 1) by Rathakrishnan and others [7,12,15,[21][22][23][24][25]. The result was very effective in terms of percentage, as micro jets reduced the base drag without affecting the wall pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Rathakrishnan [9][10][11][12][13][14][15] conducted tests for nozzles with over expansion level of 0.277. The area ratios covered were 2.56, 3.24, 4.84, and 6.25.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Rathakrishnan [10,13] conducted experiments for area ratio 3.24 and for three supersonic Mach numbers. From their tests theyachieved 95 per cent enhancementin the base pressure.…”
Section: Introductionmentioning
confidence: 99%